Spark: A Book Review - Watson, Ashleigh (The Qualitative Report, 2019)
Spark, a social research novel by Patricia Leavy, innovatively explores the complexities of doing collaborative, complex research. The story follows Sociology Professor Peyton Wilde during a week-long research seminar in Iceland with, as her invitation reads, "some of the greatest thinkers of our time." With an intriguing setup, swift plotline and lively characters, Leavy reaches to the heart of key concerns in interdisciplinary and mixed-methods research. Such concerns are well-discussed in the wider scholarly literature; Leavy uniquely handles and examines these concerns in fiction in a way that will be valuable to teachers and students alike. Spark makes an impressive contribution to fiction-based inquiry.